Kajian Karateristik Lingkungan Perumahan Tepian Sungai Dab Upaya Awal Perencanaan Model Penataan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
This study aims to identibi the characteristics of Banjarmasin riverside settlement and to formulate the preliminary model of development and conservation of the study area. The analysis which based on the field survey and some secondary data of former study shows that the role of Banjarmasin waterway as environmental symbiosis between man and nature need to be harmoniously developed and conserved. The river have many function i.e. means of transportation, place of trading, tourism and supports the settlement activities along the river. Thus, the planning criteria should be formulated for evaluating the conflicts solution in development and conservation of improvement aspects and the tourism assets utilization aspects.